Substrates and organic sources for Physalis peruviana L. seedling production - Melo, Aniela Pilar Campos de; Fernandes, Paulo Marçal; Silva-Neto, Carlos de Melo e; Souza, Eli Regina Barboza de; Guimarães, Ricardo Neves; Melo, Ariane Carla Campos de; Seleguini, Alexsander (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
The objective was to determine the effect of commercial substrates and organic sources on the production of cape gooseberry seedlings (Physalis peruviana L.). The design was completely randomized with a 2×3 factorial scheme using two commercial substrates (Carolina®, Bioplant®) and three organic sources (control, vermicompost enriched with yoorin thermophosphate and poultry manure) for seedling production. Adding poultry manure to commercial substrates negatively affects precocity and emergence. Carolina® is a suitable substrate for cape gooseberry seedling production without supplements using organic sources. Bioplant® behaves more like an emergence conditioner, requiring supplementation with organic sources (preferably vermicompost). Seedlings that are suitable for transplant can be obtained at 47 days after sowing.